The Effect Of Immigration On Productivity: Evidence From U.S. States - Peri, Giovanni (The Review of Economics and Statistics, 2012)
In this paper we analyze the long-run impact of immigration on employment, productivity, and its skill bias. We use the existence of immigrant communities across U.S. states before 1960 and the distance from the Mexican border as instruments for immigration flows. We find no evidence that immigrants crowded out employment. At the same time, we find that immigration had a strong, positive association with total factor productivity and a negative association with the high skill bias of production technologies. The results are consistent with the idea that immigrants promoted efficient task specialization, thus increasing TFP, and also promoted the adoption of unskilled-efficient technologies.